Personal and regional redistribution through the national and provincial budgets in Argentina, 2004 - Cont, Walter Alberto (2010)
This paper studies the impact of national and provincial budgets on the personal and regional distribution of income in Argentina using budget information for the year 2004, both at the aggregate (national) and disaggregate (provincial) levels. The aggregation of results hides inter-provincial effects because some province may be winner or loser in the regional distribution through the national budget and the revenue sharing regime and also because national and provincial governments use different instruments to redistribute income. The main results of the paper are summarized as follows. The aggregate effect of the consolidated public budget is a positive impact on the personal income distribution, which results from a combination of progressive expenditures and slightly regressive taxes. The impact is different depending on the province and level of government that exerts the budget. The national budget redistributes income across regions (in eight provinces the difference between expenditures and taxes is negative –they are losers in the redistribution). In spite of that, the national budget improves the personal distribution of income in all provinces. Sub-national budgets have a positive distributive impact, mostly from progressive expenditures (the most important instrument for redistribution), but also from interacting with the revenue-sharing regime, which reinforces progressivity in net-receiving provinces but creates a trade-off between progressivity and (negative) regional transfer in net-financing ones. There is no incompatibility between the redistributive effects of national and provincial budgets.